Vibrational aesthetics and education of consciousness in the process of integral health - Parode , Valquiria Pezzi (Seven Editora, 2023)
This article highlights the research on Vibrational Aesthetics (PARODE, 2004), its relationship with health and education, based on what I call, Consciousness Education for Integral Health. From an interdisciplinary and transdisciplinary qualitative approach, it brings as its foundation the holistic and integral perspective of human development, having as background references studies on Quantum Physics, Neuroscience, Transpersonal Psychology and other areas of knowledge and knowledge, in addition to theory Complexity (MORIN,2001), Multidimensionality (PARODE,2004) and Transdisciplinarity (NICOLESCU,2002). The challenge of this study is to problematize the relationship between body and consciousness, based on Vibrational Aesthetics in its applied bias. The study aims to understand the complex and empirical relationship of energy fields (emotional, mental, spiritual bodies), which are articulated with the biological physical body in the human body, in its vibrational perspective in relation to an existential projection of the being in time and space, in multi dimensions. The study also aims to highlight, through education from a perspective of Consciousness Education and Multidimensional Vibrational Therapy, the importance of processes related to the Wholeness of the Being (PARODE, 2007) for Integral Health (PARODE, 2010). Aesthetics here, beyond a theory, expands its approach to the field of pragmatic action in relation to Integral Health, enhancing a unity between body, mind, emotion and consciousness. Vibrational Aesthetics, so to speak, is the Aesthetics of Consciousness, which makes it possible, from Consciousness Education and Multidimensional Vibrational Therapy, to fully encompass body-nature-culture and cosmos as a Unit that can generate Integral Health and the fluidity of the Being in the world. In this approach to aesthetics, education and health, we identify Vibrational Aesthetics as an area of knowledge capable of generating awareness of disease prevention, for integral health, that is, of the physical and vibrational body (PARODE,2019). Through not only education for nutrition and food intake, but also for the qualification of human vibrational fields (mental, emotional and energetic). It is in this relationship between Aesthetics, Health and Education, that we perceive the vibrational field as an articulator of the different layers between the individual and their terrain, an existential locus capable of a projectual and at the same time cosmic consciousness. Hence the importance of Vibrational Aesthetics for configuring another philosophical approach regarding the issue of Health, which is multidimensional and which can certainly contribute to Integral Health and the human development of the Being in the world. DOI:https://doi.org/10.56238/sevened2023.004-061